'It was not his first Intention to swell the Work with so many Notes': Annotation in William Falconer's The Shipwreck and the birth of the Universal Dictionary of the Marine. Issue 2 (2nd April 2020) - Jones, William
Abstract : William Falconer is well known for his influential Universal Dictionary of the Marine . Less well known is that the Dictionary owed its origins to Falconer's other claim to fame as a poet . The Shipwreck (1762) is a narrative of his personal experience of a voyage, notable for its density of nautical terminology, and extensive annotation, explaining the seafaring terminology and techniques for managing a ship. The poem proved popular and two further revised editions appeared in 1764 and 1769, the year of the publication of the Universal Dictionary of the Marine . This study shows how the Universal Dictionary of the Marine owes its origins to The Shipwreck and its annotation.